The Importance of Making Use of a Syllabus of the Oral Skill in Teaching and in Teacher Training: The Case of Oral Expression Teachers at the Department of Letters and English Language, University of Constantine - Haddid, Amina (Journal of Human Sciences, 2017)
The current paper investigates the teaching ofOral Expression at the Department of Letters and English Language. It aims to find out whether there is a specific method or methodsused to teach this module and whether the teachers are provided with a syllabus to follow. Lack of a precise method and a syllabus leads to inconsistency and incoherence in teaching which are reflected in heterogeneousstudent levels of progress. It also examines the teachers’ awareness and knowledge of the different existing foreign language teaching methods and approaches, which tests the effectiveness and the reliability of their teaching practices. Finally, this paper addresses the importance of teacher training to enhance the teachers’ performance, raise their awareness of the teaching and learning processes, of how to implement a syllabus and how to remain up-to date with the latest teaching techniques and strategies.